Current-account imbalances, real exchange-rate misalignments, and output gaps - Alfonso Camba-Crespo; José García-Solanes; Fernando Torrejón-Flores (Economics: The Open-Access, Open-Assessment Journal, 2022)
This study analyzes the relationships between domestic and foreign output gaps, current-account imbalances, and real effective exchange-rate (REER) misalignments. We first set up a theoretical framework based on the elasticities and absorption approaches of the balance of payments to derive and clarify these relationships. Next, we perform panel VAR estimates in a sample of 18 advanced economies between 1986 and 2017. We find an inverse relationship between domestic output gaps and current accounts with reciprocal influences between the two variables. Moreover, we observe that increases in current accounts generally boost both temporary and structural growth. Additionally, our results indicate that REER misalignment shocks cause reactions of the opposite sign on the current account and on cyclical economic growth. We also find evidence of higher growth resulting in a real exchange-rate appreciation, which supports the Balassa-Samuelson hypothesis.
Keywords: F32; F41; F47; F49; 330; Balassa-Samuelson hypothesis; current account imbalances; output gap; PVAR; real exchange-rate misalignment